Monetary policy through production networks: Evidence from the stock market - Ali Ozdagli; Michael Weber (Federal Reserve Bank of Boston, 2017)
Monetary policy shocks have a large impact on stock prices during narrow time windows centered around press releases by the FOMC. We use spatial autoregressions to decompose the overall effect of monetary policy shocks into a direct effect and a network effect. We attribute 50 to 85 percent of the overall impact to network effects. The decomposition is a robust feature of the data, and we confirm large network effects in realized cash-flow fundamentals. A simple model with intermediate inputs allows a structural interpretation of our empirical strategy. Our findings indicate that production networks might be an important mechanism for transmitting monetary policy to the real economy.
Keywords: E12; E31; E44; E52; G12; G14; 330; input-output linkages; spillover effects; asset prices; high frequency identification; Geldpolitik; Schock; Kapitalmarktrendite; Börsenkurs; Geldpolitische Transmission; Input-Output-Analyse; Unternehmensnetzwerk; Theorie; USA